Insulin-like peptide 5 (INSL5) positively correlates with anti-Müllerian hormone (AMH) in women with the polycystic ovary syndrome: a case-control study - Yijie Chen; Miao Deng; Zhaojing Chen; Shuyang Han; Jun Chen; Hongyan Zhang; Qianwen Wang; Xuejing Jin; Wenhua Liu; Zhifen Zhang (BMC, 2022)
Abstract Background Insulin-like peptide 5 (INSL5) is involved in both reproductive and metabolic processes in polycystic ovary syndrome (PCOS). This study aimed to evaluate the relationship between INSL5 and anti-Müllerian hormone (AMH). Methods A retrospective case-control study was conducted in a university-based reproductive centre between December 2019 and January 2021. We included 117 women with PCOS and 100 healthy subjects from Zhejiang Province. All subjects were divided into four groups (1st-4th) based on quartiles of serum INSL5 levels. Serum INSL5 concentration was assayed using an enzyme-linked immunosorbent assay. Results A significant direct association was observed between serum INSL5 and AMH levels in women with PCOS. The mean AMH level in the 1st-4th INSL5 level quartiles were 4.64, 5.20, 6.46, and 9.48 ng/ml, respectively (P < 0.001). After adjusting for age, body mass index, metabolic indices, and serum levels of oestradiol and total testosterone, AMH levels remained positively and significantly associated with INSL5 levels (P for trend < 0.001). The diagnostic value of AMH was better than that of INSL5. Conclusions INSL5 and AMH levels were significantly correlated and elevated in women with PCOS. INSL5 and AMH might be associated with increased androgen secretion and chronic anovulation in PCOS.